The Glorious Excess of Peace in Marsilius of Padua's Defensor Pacis. Issue 159 (1st July 2019) - Lee Jr., Richard A.
Abstract : In Defensor Pacis Marsilius of Padua grounds the legitimacy of the kingdom, or the state (civitas), on the peace that rule provides the citizens. Looking at Aristotle's claim that the civitas strives to be like an animal in which all parts in the right proportion for the sake of health, Marsilius argues that 'the parts of the kingdom or state will be well disposed for the sake of peace [tranquilitas].' Marsilius goes on to define peace as the agreeable 'belonging together' of all members of the kingdom or the state. In this way, Marsilius moves away from a theological ground of the legitimacy of the state towards one that is entirely secular. However, the ground is an unstable one in that it acknowledges the fact that the 'members' of the body politic are characterised by difference. As such, the ground of legitimate authority will be characterised as much by force as by peace or by the relation of force to peace.